HASIL BELAJAR AKUNTANSI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS COLLABORATIVE LEARNING SISWA SMA KOTA JAMBI - Rosmiati, Rosmiati; Hutabarat, Zuhri Saputra (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2021)
The purpose of this study was to determine the effect of using a collaborative learning-based learning model on the accounting learning outcomes of class XI IPS students of SMA Negeri 5 Jambi City. This study used a quasi-experimental approach in the form of a pretest-posttest control group comparison design. The subjects in this study were students of class XI IPS 5 as the experimental class and XI IPS 3 as the control class with the data analysis technique of learning outcomes using the t-test, it can be concluded that the average accounting learning outcomes of class XI IPS students who were taught using Collaborative Learning-based learning model is 75.33 higher than the average student learning outcomes of class XI IPS on accounting subjects taught conventionally is 62.8. The results of the t-test obtained the results of the coefficient tcount> ttable or 5.048> 2.039. Thus, it can be interpreted that there is an effect of the use of Collaborative Learning-based learning models on the accounting learning outcomes of class XI IPS students at SMA Negeri 5 Kota Jambi. Keywords: Collaborative Learning-Based Learning Model, Learning Outcomes